(untitled) (Contemporary Journal of Social Science Review, 2025)
The rapid expansion of the metaverse—a network of immersive, interconnected, avatar-driven digital worlds—is reshaping how identity, agency, and power operate in virtual environments. This article conceptually examines how femininity is performed, represented, and negotiated within the metaverse, drawing on Judith Butler’s gender performativity, posthuman feminist theory, and digital embodiment. While these virtual spaces promise liberation from the constraints of physical identity, they simultaneously reproduce—and sometimes intensify—existing gendered hierarchies through algorithmic bias, avatar aesthetics, and platform economies. Recent global surveys reveal that over 60% of women-identifying users experience objectification or marginalization in immersive online spaces, and only about one in five occupy visible or leadership roles in digital creation and moderation. Through a critical synthesis of scholarship from media studies, cultural theory, and feminist digital ethics, this paper proposes the conceptual model of Performative Digital Femininity—a framework explaining how self-representation, interactive performance, and algorithmic visibility interlock in the gendered experience of cyberspace. The discussion concludes with design and policy recommendations for inclusive digital architecture, ethical avatar representation, and gender-sensitive AI governance. By reinterpreting the metaverse as both a space of limitation and a site of feminist possibility, the paper contributes to the ongoing global discourse on gender justice, digital embodiment, and posthuman identity in contemporary media culture.